Eva Österberg & Dag Lindström: Crime and Social Control in Medieval and Early Modern Swedish towns. (Almqvist & Wiksell International, 1988). 169 s., 135 SEK. - Bøgh, Anders (Historie/Jyske Samlinger, 1991)
-